2020
DOI: 10.1080/10095020.2020.1730713
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mobility data – A focus on Mobile Mapping Systems

Abstract: The increasing availability of devices to capture the position of moving objects (and other environmental information) leads to a very large amount and variety of mobility data. In order to obtain important information about the objects, their behavior or the environment of the objects, an automatic analysis is required. This article highlights current research questions in the context of the analysis of mobility data and presents them on the basis of work carried out at the Institute of Cartography and Geoinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…by deploying intelligent sensors in parking lots. Ideally, this information can be transmitted to drivers' navigation systems in search of a parking space in the form of dynamic parking maps (Zheng, Rajasegarar, and Leckie 2015;Bock 2018;Huang et al 2018;Sester 2020). In order to develop more adaptive traffic management and traveler information systems, the prediction of parking occupancy has received significant attention in recent years (Ermagun and Levinson 2018).…”
Section: Introductionmentioning
confidence: 99%
“…by deploying intelligent sensors in parking lots. Ideally, this information can be transmitted to drivers' navigation systems in search of a parking space in the form of dynamic parking maps (Zheng, Rajasegarar, and Leckie 2015;Bock 2018;Huang et al 2018;Sester 2020). In order to develop more adaptive traffic management and traveler information systems, the prediction of parking occupancy has received significant attention in recent years (Ermagun and Levinson 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile mapping system (Puente et al 2013;Li 2006;Novak 1995;Marinelli et al 2017;Sester 2020), born in the early 1990s, is one of the cutting-edge techniques of modern surveying and mapping. A mobile mapping system is the composition of global satellite positioning, inertial navigation, image processing, photogrammetry, laser scanning, geographic information, and integrated control technology.…”
Section: Introductionmentioning
confidence: 99%
“…Fusing panoramic image data collected by MMS and LiDAR data, a true color point cloud threedimensional model can be obtained, which can be applied to road target detection, high-precision map making and urban three-dimensional scene display, et al (Shao and Cai 2018;Shao, Zhang, and Wang 2017;Shao et al 2016;Shao, Wu, and Li 2021). It becomes increasingly important since the emergence of some novel techniques, such as autonomous driving, urban brain, digital twin city, et al (Shao et al 2020;Li et al 2013;Shao and Li 2011;Shams et al 2018;Li et al 2016;Craciun et al 2014;Yoshimura et al 2016;Yi and Li 2007;Sester 2020;Yang and Wang 2016;Hollick, Helmholz, and Belton 2016;Ghouaiel and Lefèvre 2016;Sun et al 2016). In this study, we have designed an MMS as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%